ETHICS AND COMMERCIAL COMMUNICATION - Flaviu MEGHIŞAN (Management & Marketing, 2014)
The modern economic science was built around the concept of efficiency. In economy the notion of equality is strongly correlated with the notion of balance, such as the market balance when the demand equals the offer. In a broader view, the economy cannot contribute to a reflection on equity unless it re-became a moral and political science or even a philosophical economy. At present, when there is an effervescence of international transactions, we all adulate the need for morality. Everyday, all around the world, regular people are affected by the costs of ethical issues. The profit and social responsibility do not exclude reciprocally. The social value of a company is given by the well-being and the work-places generated, by the products and services offered to the consumers at a fair price in correlation with the quality. The sentimental value represents the value that a person is giving to a good, based on feelings and emotions and not on monetary values. In many cases the passions and the interests are more powerful than the moral value that animates us. A lot of commercials, if they are to say the truth, would recognize that, for them, not the clients are important but the profits.